Численный анализ математических моделей распределения фактических вкладов в несимметрию и отклонение напряжений в точках общего присоединения систем электроснабжения - Саенко, Юрий Леонидович; Калюжный, Дмитрий Николаевич (НТУ "ХПИ", 2016)
На основе имитационного моделирования проведен сравнительный анализ математических моделей распределения фактических вкладов линейных источников искажений в искажение напряжений в точке общего присоединения, которые основаны на принципах наложения и исключения. Полученные результаты позволили сделать вывод об эквивалентности двух математических моделей и их произвольном выборе для решения задачи распределения фактических вкладов линейных источников искажений в искажение напряжений в точке общего присоединения.

Mathematical model for determining the factual contribution of line sources of distortion in the voltage distortion at the point of common coupling, based on the principles of superposition and exclusions, are equivalent. To assess the degree of participation of each source of distortion in the voltage distortion at the point of common coupling and distribution of financial compensation to the injured party by all sources of distortion developed a one-dimensional criteria based on the scalar product of vectors. Not accounting group sources of distortion, which belong to the subject of the energy market, to determine their total factual contribution as the residual of the factual contribution between all sources of distortion.
Numerical analysis of mathematical models of the factual contribution distribution in asymmetry and deviation of voltage at the common coupling points of energy supply systems
Keywords: качество электрической энергии; несимметрия напряжений; электроэнергия; КЭ; источник искажений; power quality; voltage asymmetry; voltage deviation